2020
DOI: 10.3390/molecules25051019
|View full text |Cite
|
Sign up to set email alerts
|

Gintonin-Enriched Fraction Suppresses Heat Stress-Induced Inflammation through LPA Receptor

Abstract: Heat stress can be caused by various environmental factors. When exposed to heat stress, oxidative stress and inflammatory reaction occur due to an increase of reactive oxygen species (ROS) in the body. In particular, inflammatory responses induced by heat stress are common in muscle cells, which are the most exposed to heat stress and directly affected. Gintonin-Enriched Fraction (GEF) is a non-saponin component of ginseng, a glycolipoprotein. It is known that it has excellent neuroprotective effects, therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
(36 reference statements)
0
17
0
Order By: Relevance
“…Mice received oral GEF (50 mg/kg/day or 150 mg/kg/day) daily for 5 weeks. Daily dosage of GEF was established referring to several studies demonstrating the bioactive effectiveness of GEF [ 22 , 29 , 30 ], and derived from the human dose (0.25 g/60 kg/day and 0.75 g/60 kg/day) in mathematical table, as described [ 31 ]. During the oral administration period, body weight and grip strength were measured weekly.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice received oral GEF (50 mg/kg/day or 150 mg/kg/day) daily for 5 weeks. Daily dosage of GEF was established referring to several studies demonstrating the bioactive effectiveness of GEF [ 22 , 29 , 30 ], and derived from the human dose (0.25 g/60 kg/day and 0.75 g/60 kg/day) in mathematical table, as described [ 31 ]. During the oral administration period, body weight and grip strength were measured weekly.…”
Section: Methodsmentioning
confidence: 99%
“…Korean ginseng (Panax ginseng Meyer, Araliaceae) is a traditional herb used in Asia to increase physical work capacity, immunity, and recovery from fatigue, and to treat inflammation [ [21] , [22] , [23] ]. Korean ginseng contains various bioactive components, including saponins (ginsenosides), non-saponin components, polysaccharides, phenolic ingredients, and alkaloids [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, as little as 12 h of heat stress in pigs was sufficient to increase muscle content of the inflammation-mediating kinase IKKα and, in turn, the phosphorylation of its nuclear target NFκB, which predictably increased gene expression for TNFα and other inflammatory cytokines [ 102 ]. A study performed in immortalized C2C12 skeletal muscle cells showed that increased expression for inflammatory cytokines may also result from greater assembly and activation of the inflammation-mediating NLRP3 inflammasome, as gene expression for all necessary components of this oligomer are increased after a 15-h period of in vitro heat stress [ 103 ]. Moreover, studies in rodents indicate that the heat shock protein HSP70 plays a key upstream role in mediating heat stress induction of inflammatory pathways [ 99 , 100 , 101 ].…”
Section: The Role Of Inflammation In Heat Stressmentioning
confidence: 99%
“…Signals were visualized using EZ-Western Lumi Femto (DoGenBio, Seoul, Korea) and quantified on a LAS-4000 (GE Healthcare Life Sciences, Marlborough, MA, USA). The intensity of the protein bands on each blot was quantified by densitometric analysis using ImageJ software (Bethesda, MD, USA) (28,29).…”
Section: Western Blottingmentioning
confidence: 99%